Menelisik Konsep Imago Dei dalam konteks Keselamatan dan Keteladanan Hidup Orang Percaya sebagai Saksi Kristus Masa Kini - Yulius Wijaya (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2024)
The Imago Dei that God gave to us from the beginning should be the basis and goal of every human being's life. The meaning of the image and likeness of God that has been damaged by sin has been restored through the redemptive work of Jesus Christ on the cross. This research is intended to see the extent of the relationship between salvation, Imago Dei and Christian life which becomes an effective means of evangelization and attracts people who do not yet know Christ and get their essence as a full human being who is happy and reaches its fullness. This research was conducted using a qualitative approach that describes how unbelievers see the Christian life in relation to the Imago Dei identity attached to it. The conclusion of this research is how believers in their lives as witnesses of Christ understand their identity as the image of God restored, live to do God's will, develop themselves correctly and bring up the character of imago Dei into a lifestyle.